Homogenization of Thin Dielectric Composite Slabs: Techniques and Limitations - Kettunen, Henrik; Qi, Jiaran; Wallén, Henrik; Sihvola, Ari (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper compares different methods for retrieving the transverse effective permittivity of periodic composite slabs whose longitudinal thickness is only a few unit cells. Two computational methods are considered, one based on simulated scattering parameters (S-parameters) and the other one based on fiel averaging by integration. The effect of frequency dispersion is studied by comparing the results with electrostatic estimates given by analytical mixing formulas. Furthermore, the influenc of the slab thickness is studied. We also discuss the boundary effects on the interfaces of the slabs.